Broadband dielectric spectroscopic detection of volatile organic compounds with ZnO nanorod gas sensors. (22nd January 2021) - Amoah, Papa K; Lin, Pengtao; Baumgart, Helmut; Franklin, Rhonda R; Obeng, Yaw S
Abstract: Metal-oxide (MO) semiconductor gas sensors based on chemical resistivity necessarily involve making electrical contacts to the sensing materials. These contacts are imperfect and introduce errors into the measurements. In this paper, we demonstrate the feasibility of using contactless broadband dielectric spectroscopy (BDS)-based metrology in gas monitoring that avoids distortions in the reported resistivity values due to probe use, and parasitic errors (i.e. tool–measurand interactions). Specifically, we show how radio frequency propagation characteristics can be applied to study discrete processes on MO sensing material, such as zinc oxide (i.e. ZnO) surfaces, when exposed to a redox-active gas. Specifically, we have used BDS to investigate the initial oxidization of ZnO gas sensing material in air at temperatures below 200 °C, and to show that the technique affords new mechanistic insights that are inaccessible with the traditional resistance-based measurements.